Self-assembly of electrospun nanofibers into gradient honeycomb structures. (15th April 2019) - Yao, Tianyu; Chen, Honglin; Samal, Pinak; Giselbrecht, Stefan; Baker, Matthew B.; Moroni, Lorenzo
Abstract: The self-assembly approach is a technically simple, rapid, and direct way to realize selective deposition of electrospun nanofibers. In the present study, we aimed to fabricate gradient polycaprolactone (PCL) honeycomb meshes by electrospinning. We demonstrated for the first time the ability to effectively fabricate a self-assembled gradient honeycomb pattern in electrospun meshes. Different honeycomb patterns were successfully fabricated by controlling the electrospinning conditions. The working distance was found to be the most important factor for the formation of gradient honeycomb structures. At a smaller working distance of 12 cm, gradients honeycomb patterns were successfully fabricated. The pore diameter of the obtained gradient honeycomb structures spanned a range from 800 μm to 300 μm. The average depth of gradient honeycomb was 123 ± 56 μm. These findings are interesting and particularly useful for us to optimize the design of gradients honeycomb scaffolds for interface tissue regeneration. Graphical abstract: Unlabelled Image Highlights: A gradient honeycomb nanofibrous mesh was fabricated by self-assembly electrospinning process. The pore diameter of the honeycomb structures can be well controlled by adjusting the working distance. The honeycomb structure can increase the depth of electrospun meshes, thus providing an additional level of surface topography.